2014
DOI: 10.1002/bmc.3106
|View full text |Cite
|
Sign up to set email alerts
|

Malva sylvestris L. extract suppresses desferrioxamine‐induced PGE2 and PGD2 release in differentiated U937 cells: the development and validation of an LC‐MS/MS method for prostaglandin quantification

Abstract: Malva sylvestris is a species used worldwide as an alternative to anti-inflammatory therapies; however, its mechanism of action remains unknown. In this paper, the anti-inflammatory effects of M. sylvestris alcoholic extracts were evaluated by measuring the pro-inflammatory mediators PGE₂ and PGD₂ in desferrioxamine-stimulated phorbol 12-myristate 13-acetate-differentiated U937 cells. An HPLC-DAD fingerprint of the M. sylvestris extract was performed and caffeic acid, ferulic acid and scopoletin were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Complementary to the results observed for leaves, crude extracts of flowers showed statistically ( p < 0.05) lower values at 50 µg/mL for PGE 2 , PGD 2 , and PGF 2α , showing that leaves and flowers together are able to inhibit all the prostanoids tested. Similar findings were observed in the literature for M. sylvestris in the U937-d cell line [ 25 ]. Inhibition higher than 30% was observed for at least one mediator for all extracts or fractions.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Complementary to the results observed for leaves, crude extracts of flowers showed statistically ( p < 0.05) lower values at 50 µg/mL for PGE 2 , PGD 2 , and PGF 2α , showing that leaves and flowers together are able to inhibit all the prostanoids tested. Similar findings were observed in the literature for M. sylvestris in the U937-d cell line [ 25 ]. Inhibition higher than 30% was observed for at least one mediator for all extracts or fractions.…”
Section: Resultssupporting
confidence: 92%
“…Analysis of the extract showed the main compounds present on it are scopoletin, quercetin and malvidin 3-glucoside, but the authors attributed the observed effect to malvidin 3-glucoside. Leaf extract of M. sylvestris showed in vitro anti-inflammatory activity, demonstrated the presence of the compounds scopoletin, caffeic acid and ferulic acid [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it was confirmed that malvidin 3‐glucoside appears to be the main responsible bioactive compound for the antiinflammatory effect (Prudente et al, ). Also, Martins et al suggested that M. sylvestris extracts antiinflammatory effects seem to be related to special antiinflammatory mediators induction—prostaglandins PGE 2 and PGD 2 (Martins et al, ). Besides, several studies documented wound healing effects to M. sylvestris .…”
Section: Pharmacological Properties Of Malva Plantsmentioning
confidence: 99%
“…Many studies have examined mallow and proposed numerous properties for this herb. Extracts from mallow leaves show anti-complementary properties [ 15 ], suppress release of pro-inflammatory mediators PGE2 and PGD2 [ 16 ], and have anti-inflammatory properties [ 17 21 ].…”
Section: Introductionmentioning
confidence: 99%